SECTION II Veterinary Oncology. Research papers and case reports.: Veterinary Oncology. Research papers and case reports. (Veterinary Science, 2022)
Oncología Veterinaria. COMISION ACADEMICA Y CIENTIFICAMV. de Genaro, Mariana ( Práctica privada)Dr. Lorenzutti, Matías (Universidad Católica de Córdoba)Esp. Miguel, María Carolina (Universidad Nacional de La Pampa)Dr. Nejamkin, Pablo ( Universidad Nacional del Centro de la Pcia. de Buenos Aires)Dr. Otero, Pablo (Universidad de Buenos Aires)MV Robledo, Oscar ( Universidad Nacional de La Plata)Dr. Tarragona, Lisa (Universidad de Buenos Aires)
Keywords: Minimally invasive surgery; Intestinal cyst; Canine transmissible venereal tumor; Vincristine; Nasal carcinoma; Post inoculation sarcoma; Lymphoma; Additive manufacturing; Resistance; Chemotherapy; Radiotherapy; Stage IV; Adjuvant; Panniculitis; Canine; mmunohistochemistry; Prosthesis; Biomimicry; Pericardiectomy; Thorax; Pleura; Dog; Duplication; Elderly